The main drivers of labour cost dynamics in Central and Eastern European countries - Maria Denisa VASILESCU; Larisa STĂNILĂ; Amalia CRISTESCU; Maria Berta BELU; Silvana CRIVOI (Theoretical and Applied Economics, 2025)

(untitled)
Labour costs are a fundamental component of production expenses, significantly impacting both the quantity and quality of output. In the current European economic context marked by significant price increases, the paper aimed to empirically investigate the relationship between inflation and labour costs in the short and medium term. We focused on the situation in Romania and three other Central and Eastern European countries: the Czech Republic, Hungary, and Poland. We applied the Granger causality test to determine the direction of causality between the two indicators mentioned. We also performed a regression analysis to gain a more in-depth understanding. The results highlighted the existence of a causal relationship from inflation to labour costs at both aggregate and sectoral levels, with variations across countries and sectors, supporting the hypothesis that inflation precedes increases in labour costs. To explore the determinants of labour costs in more depth, we estimated regression models for three of the analysed countries. The results indicated that past labour cost values, inflation, and labour productivity are the main drivers of labour cost dynamics in Romania, the Czech Republic, and Hungary. Additionally, the share of exports in GDP and the employment rate influence labour costs in Hungary and the Czech Republic, but with distinct country-specific patterns.